RAWI MURJI’AH IN S{AH{In’s Transmission in S{ah{i>h} al-Bukha>ri>) - Ihsan Humaedi (Diroyah : Jurnal Studi Ilmu Hadis, 2020)
This article will discuss the hadith narratives of a person who is considered an expert bid'ah and Imam al-Bukha> ri> load it into the book al-S}ah}i>h}. Using the literature study, this article found that among the hereditary experts contained in S{ah{i>h} al-Bukha>ri is the one named 'Abd al-H{ami>d bin ‘Abd al-Rah}ma>n al-H{imma>ni> indicated includes the Murji'ah group and the scholars differing in their views on the status of the heresy experts, some of them claiming to reject the heresy of the heresy because the requirements of the hadith s}ah}i>h} are not fulfilled that is in the 'adl aspect. Some other scholars see that it can be accepted by bid'ah expert transmission with a condition; rawi do not include people who are considered to lie and transmission does not have a motive for heresy. Then this paper will discuss the transmitter named 'Abd al-H{ami>d bin 'Abd al-Rah}ma>n al-H{imma>ni and his transmission in the book al-S}ah}i>h} accordingly with the concept of assessment of heresy experts.